#TITLE_ALTERNATIVE# - RIDWAN FAUZI (NIM : 15209001), MOCHAMAD
North Lombok is a region that has a variety of attractions such as mountains, waterfalls, traditional villages, small islands, and beaches. One of the attractions being developed is a tourist area named Sire Medana. The area is tend to quiet but has an interesting natural potential such as Sire Indah beach, scenery in Gili Tramena, views of Gunung Agung, the beauty of the sunset and lined palm trees. These potentials attract private sectors to invest on resort hotels. This project aims to design a hospitality facility, which can be a choice for both domestic and foreign travelers. From the issue of resort hotel specifically the function, the atmosphere and the locality, obtained that the focus problem is how to maximize the potential of land that has a view of the sea, a lot of palm trees and create a resort hotel that can accentuate the locality of Lombok. Therefore, the buildings in this resort hotel are placed by the chance formed of palm trees, whereas the local Lombok image is raised from the interpretation of traditional buildings.